Cu (II) and ammonium adsorption from dairy cattle breeding sewage by phosphorus-modified dairy cow manure hydrochar - Yang, Zhendong; Tong, Min; He, Xueqin; Han, Lujia; Guo, Jianbin; Jing, Tianjun; Huang, Guangqun; Shi, Changming (International Journal of Agricultural and Biological Engineering, 2022)
To realize the synergistic treatment of dairy cow manure solids and dairy cattle breeding sewage, this study produced phosphorus-modified hydrochar by dairy cow manure solids impregnated with potassium phosphate (K3PO4). And then, the adsorption characteristics of Cu (II) and ammonium (NH4+) in dairy cattle breeding sewage under different dosages and adsorption time conditions of modified hydrochar were explored. The results show that the specific surface area and total pore volume of the hydrochar were increased by phosphorus-modified. The adsorption amount of hydrochar per unit-mass decreased with the increase in the dosage. With the increase in the dosage, the adsorption capacity of Cu (II) decreased from the initial 26.16 mg/g to 3.38 mg/g. The adsorption of Cu (II) and NH4+ in sewage by hydrochar was mainly chemical adsorption, which was mainly affected by chelation and ion exchange. This adsorption was more inclined to single-molecular layer adsorption. Both the pH values and the ionic strength influenced the competitive adsorption between Cu (II) and NH4+. The higher the pH value was, the greater the adsorption amount, and the stronger the adsorption capacity by hydrochar. Moreover, the increase in the ionic strength decreases the adsorption capacity of hydrochar.Keywords: dairy manure, hydrochar, sewage, adsorption, competitive adsorptionDOI: 10.25165/j.ijabe.20221505.7640Citation: Yang Z D, Tong M, He X Q, Han L J, Guo J B, Jing T J, et al. Cu (II) and ammonium adsorption from dairy cattle breeding sewage by phosphorus-modified dairy cow manure hydrochar. Int J Agric & Biol Eng, 2022; 15(5): 78–84.